THU0295 Interleukin-6 and Soluble Interleukin-6 Receptor in Large-Vessel Vasculitides. (9th June 2015) - Pulsatelli, L.; Dolzani, P.; Assirelli, E.; Meliconi, R.; Pipitone, N.; Muratore, F.; Pazzola, G.; Boiardi, L.; Salvarani, C.
Abstract : Background: A role for interleukin-6 (IL-6) in the pathogenesis of large-vessel vasculitides (LVV) has been suggested by previously reported results indicating increased serum IL-6 levels in patients compared to healthy controls (1, 2). In addition, IL-6 relevance in LVV is also supported by genetic evidence, as highlighted by a very recent study reporting an association of specific IL-6 gene polymorphism with Takayasu's arteritis (TA) susceptibility (3). IL-6 mediates its functions through two membrane proteins: the IL-6 receptor (IL-6R) and gp130, the signal transducing element. Soluble form of IL-6R (sIL-6R), after binding with IL-6, is able to associate to membrane gp130 and mediate intracellular signalling in IL-6R negative cells. The biological activity of IL-6 strictly depends on the interrelationship occurring among these molecules and the role of sIL-6R as an inflammatory biomarker has been recognized in several diseases. Objectives: Since, to date, reliable biomarkers for assessing clinical activity in LVV are lacking, we aimed to investigate serum levels of IL- 6 and IL-6R in patients with Giant Cell Arteritis (GCA) and TA, in order to evaluate their relationship with disease activity assessed by 18F-fluorodeoxyglucose-positron emission tomography/computed tomography (18F-FDG PET/CT) and by clinical indices including National Institutes of Health-NIH/Kerr criteria and Indian Takayasu Activity Score (ITAS). Methods: Sera were obtained from 72 patients with LVV (33 GCA and 39 TA) who underwent a PET/CT scan and from 60 age-matched normal controls (NC). PET/CT scans were reviewed by a nuclear medicine physician who had no knowledge of the clinical information. Vascular uptake was graded using a 4 point semiquantitative scale. ITAS, Kerr/NIH scores and sera for serum biomarker investigations were obtained within 20 days of the PET/CT scans.IL-6 and sIL-6R serum levels were evaluated using commercial DuoSet ELISA kits (R&D Systems) following the manufacturer's instruction. Results: IL-6 and sIL-6R serum levels were significantly higher in both GCA and TA patients compared to NC (IL-6: GCA vs NC p<0.005, TA vs NC p<0.0001; sIL-6R: GCA vs NC: p<0.0005, TA vs NC: p<0.01). No significant difference was found between serum levels of GCA patients compared to TA patients. When stratifying LVV patients according to PET/CT assessment, no difference was seen between IL-6 and IL-6R levels in patients with an active scan compared to those with an inactive scan in both LVVs. Similarly, according to both ITAS and NIH/Kerr scores, no difference was found between the soluble factor levels in patients with active disease compared to inactive patients. Conclusions: IL-6 and sIL-6R were elevated in large-vessel vasculitis (TA and GCA) compared to NC, but neither soluble factor appeared to be associated with disease activity assessed both by PET/CT scan and clinical scores (Kerr-NIH and ITAS scores). References: Park MC et al., Rheumatology 2006. 2. Alibaz-Oner F et al., Clinical and Experimental Rheumatology, in press. 3. Renauer P et al, Arthritis Rheumatol 2015 Disclosure of Interest: None declared